Voice-based user interface as a tool to promote foreign language teaching/learning (Revista Brasileira de Contabilidade e Gestão, 2012)
This paper presents a study of the use of Voice User Interface (VUI) to aid on foreign language learning – to improve the listening, understanding and pronunciation of English language. Using recognition and synthesis voice technology, an application called VAL is built; this application follows a specific methodology for developing VUI applications.
Keywords: voice user interface; foreign language teaching; human-computer interface